Experimental investigation of emissions from a single-cylinder diesel engine using methanol–diesel blends - Kadhim, Mohammed Qays; Oshchepkov, Petr Platonovich (Frontiers in Energy Research, 2024)
This study examines the effects of methanol–diesel blends on the emissions of a diesel engine, concentrating on carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides (NOx), hydrocarbons (HCs), and particulate matter (PM). Using a single-cylinder four-stroke diesel engine at varying torque settings (2 N m–6 N m), significant reductions in CO, CO2, HC, and PM emissions were observed with increasing methanol content. CO emissions reduced by up to 81.8%, CO2 by up to 64.2%, HC by up to 80.4%, and PM by up to 23.5% with the MD11 blend. NOx emissions initially increased but decreased by up to 20% at higher torques with the same blend. These results highlight the environmental benefits of methanol–diesel blends and the need for effective NOx reduction strategies.